Health Diagnosis of School Leadership in the Implementation of Digital-Based - Suryadi, Suryadi; Triana, Cepi; Sudarsyah, Asep (PEDAGOGIA, 2024)
The digital-based school leadership health diagnosis is a continuation of previous research that developed concepts and instruments for diagnosing school leadership health. The application created in this study utilizes a streamlined process based on the first five stages of Borg and Gall's model, which aims to produce an efficient diagnostic tool. Initially, the application included five stages: self-evaluation, interviews, observations, preparation of recommendations, and implementation of recommendations. However, through limited trials, the diagnosis stages were reduced from five to four, by eliminating the observation stage. The refined process now consists of self-evaluation, interviews, preparation of recommendations, and implementation of recommendations. It was observed that the objectives of the removed observation stage could still be effectively met during the interview process, where the validation, analysis, and discussion of leadership health issues were conducted. This digital application demonstrates an enhanced capacity for diagnosing school leadership health in a more efficient and streamlined manner, without compromising the accuracy of the diagnosis. The results of this study indicate that the application successfully reduces the time needed for analysis while maintaining a high level of diagnostic precision.